An Integrative Review of Flipped Classroom Teaching Models in Nursing Education - Njie-Carr, Veronica P.S.; Ludeman, Emilie; Lee, Mei Ching; Dordunoo, Dzifa; Trocky, Nina M.; Jenkins, Louise S. (Journal of professional nursing, 2017)
Nursing care is changing dramatically given the need for students to address complex and multiple patient comorbidities. Students experience difficulties applying knowledge gained from didactic instruction to make important clinical decisions for optimal patient care. To optimize nursing education pedagogy, innovative teaching strategies are required to prepare future nurses for practice. This integrative review synthesized the state of the science on flipped classroom models from 13 empirical studies published through May 2016. The purpose of the review was to evaluate studies conducted on flipped classroom models among nursing students using a validated framework by Whittemore and Knafl. Multiple academic databases were searched, ranging in scope including PubMed, Embase (Elsevier), CINAHL (Ebsco), Scopus, Web of Science, and Google Scholar, resulting in 95 unique records. After screening and full-text reviews, 82 papers were removed. Thirteen empirical studies were included in the final analysis and results provided (a) design and process information on flipped classroom models in nursing education, (b) a summary of the state of the evidence to inform the implementation of flipped classrooms, and (c) a foundation to build future research in this area of nursing education. To develop sound evidence-based teaching strategies, rigorous scientific methods are needed to inform the implementation of flipped classroom approaches. •Flipped technology-enhanced pedagogy promotes active learning and critical thinking.•Rigorous studies are needed that are focused on flipped classroom models in nursing.•Lessons learned from other disciplines can be integrated to inform implementation.•Studies are needed to determine long-term effects in clinical performance.•Teaching assignments and demands for technologic resources should be considered.